2017
DOI: 10.1002/mmce.21129
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wide band antenna attachable on UAV surface

Abstract: In the present study, ultra‐wide band antenna attachable on unmanned aerial vehicle (UAV) surfaces usable as signal detection antenna in various bands was designed, and the practicality of the developed antenna was verified by attaching the antenna to a UAV and measuring the performance. The antenna suggested in this article was manufactured by forming a hemispheric conductor having the shape of a baseball seam on the ground and satisfying a self‐complementary through an image theory. This Hemispheric shape ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For the two bands, the antenna was designed to have omnidirectional and quasi-omnidirectional radiation characteristics, respectively. A hemispheric conductor seamed on a 0.8 × 0.8λ 2 ground for Ultra wideband UAV applications is reported in [11]. While in [12], higher-order mode circular patch antenna operating in the frequency range of 674-719MHz was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For the two bands, the antenna was designed to have omnidirectional and quasi-omnidirectional radiation characteristics, respectively. A hemispheric conductor seamed on a 0.8 × 0.8λ 2 ground for Ultra wideband UAV applications is reported in [11]. While in [12], higher-order mode circular patch antenna operating in the frequency range of 674-719MHz was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The studies for UAV antenna have been reported in some literature. [1][2][3][4][5][6][7] Although there can be some criteria in grouping the antenna for UAV, the antenna types in those articles can be categorized into two groups, namely bladetype group and surface-mounted type group.…”
Section: Introductionmentioning
confidence: 99%
“…Good aerodynamic characteristics can be expected and beam-steering is possible by arraying, but the bandwidth is narrow, a control circuit is required for beam-steering and the space inside the wings for antenna array formation and feeding cannot be acquired easily. Other articles [5][6][7] show the surface-mount type antennas or conformal type antennas.…”
Section: Introductionmentioning
confidence: 99%